SPECTROPHOTOMETRIC QUANTIFICATION OF TOTAL PHENOLIC, FLAVONOID, AND ALKALOID CONTENTS OF ABRUS PRECATORIUS L. SEEDS - Tabasum, Shazia; Khare, Swati; Jain, Kirti (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of the present work was to assess the total phenolic content (TPC), total flavonoid content (TFC), and total alkaloid content (TAC) of crude hydro-methanolic seed extract of Abrus precatorius L. which is one of the beautiful seed bearing plant belonging to family Fabaceae and used extensively in many Ayurvedic preparations with significant therapeutic significance. Methods: The amount of total phenols was analyzed using Folin–Ciocalteu assay, the amount of total flavonoids by aluminum chloride assay and total alkaloids by bromocresol green-complex assay. Results: The TPC, TFC, and TAC of the hydro-methanolic seed extract were 219.966±4.714 mg gallic acid equivalent per gram, 73.333±2.357 rutin equivalent per gram, and 41.666±4.784 atropine equivalent per gram, respectively. Conclusion: The result of the study highlighted a potent phenol, flavonoid, and alkaloid contents in the crude extract and thus can be used to explore new drugs. The study also justifies some of the medicinal properties of the plant. Keywords: Abrus precatorius, Spectrophotometry, Total phenolic content, Total flavonoid content, Total alkaloid content.